FORCES END MEANS IN SYSTEM ZENITHAL of ROCKET COVERING of MILITARY OBJECTS - Yermoshin, М. О. (Honor and Law, 2019)
In the article the offers by definition іnterrelations between quantity of forces and means of a grouping zenithal of rocket armies and system zenithal of rocket covering of military objects have been examined.